The Consequences of an Embargo on Russian Gas - Veronika Grimm; Andreas Löschel; Karen Pittel (Wirtschaftsdienst)
Abstract Sanctions and their effectiveness are at the centre of the discussion about an appropriate response to Russia’s war of aggression against Ukraine. At the latest since the atrocities of the war became evident and payment for gas supplies in roubles was brought into play, voices calling for a natural gas embargo have been growing. In the discussion about the possible consequences of such an embargo, forecasts vary from serious but manageable effects on economic development to mass unemployment and deindustrialisation. Regarding the short run, the main question is: How much of Russian natural gas supply can be replaced and saved by next winter. We provide an overview of existing analyses on savings and substitution potentials, followed by some fundamental policy principles aimed at dealing with a halt in Russian natural gas supplies.